RAIN study: a protocol for a randomised controlled trial evaluating efficacy, safety and cost-effectiveness of intravenous-to-oral antibiotic switch therapy in neonates with a probable bacterial infection - Fleur M Keij; René F Kornelisse; Nico G Hartwig; Katya Mauff; Marten J Poley; Karel Allegaert; Irwin K M Reiss; Gerdien A Tramper-Stranders (BMJ Open)
Introduction High morbidity and mortality rates of proven bacterial infection are the main reason for substantial use of intravenous antibiotics in neonates during the first week of life. In older children, intravenous-to-oral switch after 48 hours of intravenous therapy has been shown to have many advantages and is nowadays commonly practised. We, therefore, aim to evaluate the effectiveness, safety and cost-effectiveness of an early intravenous-to-oral switch in neonates with a probable bacterial infection.Methods and analysis We present a protocol for a multicentre randomised controlled trial assessing the non-inferiority of an early intravenous-to-oral antibiotic switch compared with a full course of intravenous antibiotics in neonates (0–28 days of age) with a probable bacterial infection. Five hundred and fifty patients will be recruited in 17 hospitals in the Netherlands. After 48 hours of intravenous treatment, they will be assigned to either continue with intravenous therapy for another 5 days (control) or switch to amoxicillin/clavulanic acid suspension (intervention). Both groups will be treated for a total of 7 days. The primary outcome will be bacterial (re)infection within 28 days after treatment completion. Secondary outcomes are the pharmacokinetic profile of oral amoxicillin/clavulanic acid, the impact on quality of life, cost-effectiveness, impact on microbiome development and additional yield of molecular techniques in diagnosis of probable bacterial infection.Ethics and dissemination This study has been approved by the Medical Ethics Committee of the Erasmus Medical Centre. Results will be presented in peer-reviewed journals and at international conferences.Trial registration number NCT03247920